TO COMPARE THE EFFECTIVENESS OF INTRAVENOUS WITH ORAL IRON IN NON-DIALYSIS DEPENDENT PATIENTS OF CHORONIC KIDNEY DISEASE. - Ijaz Nabi; Muhammad sohail; Sumara Tabassam et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT:OBJECTIVE: To compare the eﬃcacy of oral iron with intravenous iron in non-dialysis dependent patients of chronic kidney disease in terms of hemoglobin (Hb) increase of more than 1g/dl. STUDY DESIGN: Randomized control trial. PLACE AND DURATION OF STUDY: Department of Nephrology, Allied Hospital Faisalabad, from October 2015 to March 2016. METHODOLOGY: 214 patients with chronic kidney disease who were not on dialysis and who fulﬁlled the criteria for iron deﬁciency anemia were included in the study. The population was randomized into two groups. Patients in the intravenous (i/v) iron group were given injection iron sucrose 1 gram in ﬁve divided doses while patients in the oral iron group were given tablet ferrous sulphate 200mg three times daily. Hb was checked after 40 days. Eﬀect modiﬁers like age and gender were controlled by stratiﬁcation. The Chi-square test was applied for categorical variable association. The Paired t-test was applied to compare the hemoglobin level before and after the treatment. P-value ≤ 0.05 was taken as signiﬁcant. RESULT: Minimum (min) age was 15 years and maximum (max) age was 80 years with mean age of 49.57± 15.89 years. Min Hb at baseline was 4.2 g/dl and max was 11.8 /dl with a mean Hb of 8.32±1.17 g/dl. Min Hb after 40 days of treatment was 5.5 g/dl and max Hb was 11.7 g/dl with a mean Hb of 9.007 ±1.20 g/dl. After 40 days of treatment 75 patients (35%) had an increase of Hb by 1g/dl. Out of these 75 patients 28(26.2%) were in the oral iron group and 47(43.9%) were in i/v group. The chi square value for eﬃcacy was 7.410 and p-value was 0.006. In i/v iron group the mean Hb at baseline was 8.210±1.1363 g/dl and after 40 days it was 9.030±1.2014 g/dl with a pvalue of 0.0001. In oral iron group mean Hb at baseline was 8.430±1.2008 g/dl and after 40 days it was 8.985±1.2211 g/dl with a p-value of 0.0001. CONCLUSIONS: Iron replacement in ND-CKD patients increases the mean Hb levels signiﬁcantly however i/v iron is more eﬃcacious than oral iron in terms of Hb increase by 1g/dl till day 40.